Sustainable Designed Pavement Materials - Xiao, Yue; Erkens, Sandra; Li, Mingliang; Ma, Tao; Liu, Xueyan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue "Sustainable Designed Pavement Materials" has been proposed and organized as a means to present recent developments in the field of environmentally-friendly designed pavement materials. For this reason, articles included in this special issue relate to different aspects of pavement materials, from industry solid waste recycling to pavement materials recycling, from pavement materials modification to asphalt performance characterization, from pavement defect detection to pavement maintenance, and from asphalt pavement to cement concrete pavement.